Investigation on physical, mechanical and wettability properties of 3D printed polyamide-12 membrane - Arbain, Nurul Afiqah (2025)
Three dimensional (3D) printed polymer membrane is highly feasible for gravity-driven, oil-water separation for oil spill remediation due to its reliable selective separations, high efficiency and switchable wettability. However, its underwater switchable wettability can be a challenge due to printing parameters; any surface alteration will modify the printed membrane wettability, enhanced by the influence of water temperature which can destabilize underwater superoleophobicity of the printed membrane. This study aimed to analyse the printing parameters’ effect on underwater switchable wettability in elevated water temperatures to improve the wettability of printed polymer membranes. For surface hydrophobicity improvement, printed polyamide membranes were immersed in a hydrophobic-candle soot/hexane mixture and subjected to sonication process. The parameters of ‘dry’ wettability, morphology, porosity, surface roughness and mechanical properties of the membranes were evaluated; the 3D printing parameters effect was also assessed. Moreover, this study uniquely examines the impact of printing parameters on underwater switchable wettability across a temperature range of 30 to 50°C. The underwater superoleophobicity of the printed polymer membranes was analysed by the oil droplet underwater contact angle measurement in the inverted sessile drop experimental setup. CM-2 B specimen (bottom surface of coated membrane specimen fabricated from 70 W of laser power and 0.12 mm of layer thickness) showed the best wettability performance with the highest water contact angle (WCA) value of 150.65°, achieving superhydrophobic behaviour. This was due to the specimen having the highest surface roughness and porosity values of 11.14 µm and 22.37 %, respectively. The increase in surface roughness increases the WCA on the membrane. For the tensile properties, the NCM-3 specimen (non-coated membrane specimen fabricated from 80 W of laser power and 0.06 mm of layer thickness) obtained the highest values (42.40 MPa) due to higher energy density (ED) transmitted during the printing process influenced by the printing parameter setting. However, the highest oil-water separation efficiency was recorded by CM-2 B specimen with 99.5%. For the underwater oil contact angle (OCA), CM-2 B specimen recorded the highest OCA values (160.56°) at 30°C. Nevertheless, as the water temperatures rose to 40°C and 50°C, OCA values for CM-2 B specimen decreased from 155.75° to 153.66 °, a similar trend for all specimens. The proposed underwater OCA model reveals that the temperature negatively affects OCA (-0.2959), while layer thickness has a strong positive influence (79.90). The ANOVA results also highlighted temperature and layer thickness as the most significant predictors for underwater OCA. From this study, it has been shown that printing parameters, surface modification and temperatures affect the performance of the membrane especially in oil-water separation process.